Stacked cylinders inscribed in a cone!

Geometry Level 4

Extend the above diagram to an infinite number of stacked right circular cylinders inscribed in the above right circular cone.

Let S S represent the total volume of all the cylinders and V c o n e V_{cone} be the volume of the cone.

If S V c o n e = a b \dfrac{S}{V_{cone}} = \dfrac{a}{b} , where a a and b b are coprime positive integers, find a + b a + b .

Note: The initial right circular cylinder is the largest right circular cylinder that is inscribed in the above right circular cone. Each consecutive right circular cylinder is the largest right circular cylinder that can be inscribed in the remaining right circular cone.


The answer is 31.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let the base radius and height of the cylinder be r r and h h and those of the inscribed cylinder be x x and y y . Then we note that y r x = h r y = h h r x \dfrac y{r-x} = \dfrac hr \implies y = h - \dfrac hr x and the volumn of the cylinder is V = π x 2 y = π x 2 ( h h r x ) V = \pi x^2y = \pi x^2\left(h - \dfrac hrx\right) . To find V max V_{\max} , d V d x = π h ( 2 x 3 x 2 r ) \dfrac {dV}{dx} = \pi h \left(2x - \frac {3x^2}r\right) . Equating d V d x = 0 \dfrac {dV}{dx} = 0 , x = 2 3 r \implies x = \dfrac 23 r , y = 1 3 h y = \dfrac 13h , and V max = π ( 2 3 r ) 2 h 3 = 4 9 V cone V_{\max} = \pi \left(\dfrac 23r\right)^2 \cdot \dfrac h3 = \dfrac 49 V_{\text{cone}} , since V cone = 1 3 π r 2 h V_{\text{cone}} = \dfrac 13 \pi r^2 h .

Let V cone = V 1 V_{\text{cone}} = V_1 and the subsequence volumes of smaller cones be V 2 , V 3 , V 4 , V_2, V_3, V_4, \cdots . Since y = 1 3 h y = \dfrac 13 h , then the height of the next smaller similar cone is 2 3 h \dfrac 23 h . Therefore V 2 V 1 = ( 2 3 ) 3 = 8 27 \dfrac {V_2}{V_1} = \left(\dfrac 23\right)^3 = \dfrac 8{27} . As the patent repeats, we have V n V n + 1 = 8 27 \dfrac {V_n}{V_{n+1}} = \dfrac 8{27} .

Then the sum of volumes of all cylinder is:

S = 4 9 V 1 + 4 9 V 2 + 4 9 V 3 + 4 9 V 4 + = 4 9 ( V 1 + V 2 + V 3 + V 4 + ) = 4 9 V cone ( 1 + 8 27 + ( 8 27 ) 2 + ( 8 27 ) 3 + ) S V cone = 4 9 1 1 8 27 = 12 19 \begin{aligned} S & = \dfrac 49 V_1 + \dfrac 49 V_2 + \dfrac 49 V_3 + \dfrac 49 V_4 + \cdots \\ & = \dfrac 49 (V_1 + V_2 + V_3 + V_4 + \cdots) \\ & = \dfrac 49 V_{\text{cone}} \left(1 + \frac 8{27} + \left(\frac 8{27} \right)^2 + \left(\frac 8{27} \right)^3 + \cdots \right) \\ \implies \frac S{V_{\text{cone}}} & = \dfrac 49 \cdot \frac 1{1-\frac 8{27}} = \frac {12}{19} \end{aligned}

Therefore a + b = 12 + 19 = 31 a+b = 12+19 = \boxed{31} .

Rocco Dalto
Oct 4, 2020

Let R 1 R_{1} and r 1 r_{1} be the radius of the cone and the initial cylinder and H 1 H_{1} and h 1 h_{1} be the height of the cone and the initial cylinder.

V c o n e = π 3 R 1 2 H 1 V_{cone} = \dfrac{\pi}{3}R_{1}^2H_{1} and V 1 = π r 1 2 h 1 V_{1} = \pi r_{1}^2h_{1} the volume of the initial cylinder.

From the above diagram we have the proportion:

R 1 R 1 r 1 = H 1 h 1 h 1 = H 1 R 1 ( R 1 r 1 ) V 1 = π H 1 R 1 ( R 1 r 1 2 r 1 3 ) \dfrac{R_{1}}{R_{1} - r_{1}} = \dfrac{H_{1}}{h_{1}} \implies h_{1} = \dfrac{H_{1}}{R_{1}}(R_{1} - r_{1}) \implies V_{1} = \dfrac{\pi H_{1}}{R_{1}}(R_{1}r_{1}^2 - r_{1}^3) \implies

d V 1 d r 1 = π H 1 R 1 ( 2 R 1 3 r 1 ) = 0 \dfrac{dV_{1}}{dr_{1}} = \dfrac{\pi H_{1}}{R_{1}}(2R_{1} - 3r_{1}) = 0 and r 1 0 r 1 = 2 3 R 1 h 1 = 1 3 H 1 r_{1} \neq 0 \implies \boxed{r_{1} = \dfrac{2}{3}R_{1}} \implies \boxed{h_{1} = \dfrac{1}{3}H_{1}}

H 2 = H 1 h 1 = 2 3 H 1 H_{2} = H_{1} - h_{1} = \dfrac{2}{3}H_{1} and r 1 r 1 r 2 = H 2 h 2 h 2 = H 2 r 1 ( r 1 r 2 ) \dfrac{r_{1}}{r_{1} - r_{2}} = \dfrac{H_{2}}{h_{2}} \implies h_{2} = \dfrac{H_{2}}{r_{1}}(r_{1} - r_{2})

V 2 = π H 2 r 1 ( r 1 r 2 2 r 2 3 ) \implies V_{2} = \dfrac{\pi H_{2}}{r_{1}}(r_{1}r_{2}^2 - r_{2}^3) \implies d V 2 d r 2 = π H 2 r 1 r 2 ( 2 r 1 3 r 2 ) \dfrac{dV_{2}}{dr_{2}} = \dfrac{\pi H_{2}}{r_{1}} r_{2}(2r_{1} - 3r_{2}) and r 2 0 r_{2} \neq 0 \implies

r 2 = 2 3 r 1 = ( 2 3 ) 2 R 1 h 2 = H 2 r 1 ( 2 3 4 9 ) R 1 = H 2 r 1 ( 2 9 ) R 1 = 2 H 1 3 3 2 R 1 ( 2 9 ) R 1 = r_{2} = \dfrac{2}{3}r_{1} = (\dfrac{2}{3})^2 R_{1} \implies h_{2} = \dfrac{H_{2}}{r_{1}}(\dfrac{2}{3} - \dfrac{4}{9})R_{1} = \dfrac{H_{2}}{r_{1}}(\dfrac{2}{9})R_{1} = \dfrac{2H_{1}}{3} * \dfrac{3}{2R_{1}}(\dfrac{2}{9})R_{1} = 2 9 H 1 = 1 3 ( 2 3 ) H 1 \dfrac{2}{9}H_{1} = \dfrac{1}{3}(\dfrac{2}{3}) H_{1}

r 2 = ( 2 3 ) 2 R 1 \therefore \boxed{r_{2} = (\dfrac{2}{3})^2 R_{1}} and h 2 = 1 3 ( 2 3 ) H 1 \boxed{h_{2} = \dfrac{1}{3}(\dfrac{2}{3}) H_{1} }

H 3 = H 2 h 2 = 4 9 H 1 H_{3} = H_{2} - h_{2} = \dfrac{4}{9}H_{1} and r 2 r 2 r 3 = H 3 h 3 h 3 = H 3 r 2 ( r 2 r 3 ) \dfrac{r_{2}}{r_{2} - r_{3}} = \dfrac{H_{3}}{h_{3}} \implies h_{3} = \dfrac{H_{3}}{r_{2}}(r_{2} - r_{3}) \implies

V 3 = π H 3 r 2 ( r 2 r 3 2 r 3 3 ) V_{3} = \dfrac{\pi H_{3}}{r_{2}}(r_{2}r_{3}^2 - r_{3}^3) \implies d V 3 r 3 = π H 3 r 2 r 3 ( 2 r 2 3 r 3 ) = 0 \dfrac{dV_{3}}{r_{3}} = \dfrac{\pi H_{3}}{r_{2}} r_{3}(2r_{2} - 3r_{3}) = 0 and r 3 0 r_{3} \neq 0 \implies

r 3 = 2 3 r 2 = ( 2 3 ) 3 R 1 h 3 = H 3 r 2 ( 4 9 8 27 ) R 1 = H 3 r 2 ( 4 27 ) R 1 = r_{3} = \dfrac{2}{3}r_{2} = (\dfrac{2}{3})^3 R_{1} \implies h_{3} = \dfrac{H_{3}}{r_{2}}(\dfrac{4}{9} - \dfrac{8}{27})R_{1} =\dfrac{H_{3}}{r_{2}}(\dfrac{4}{27})R_{1} =

4 H 1 9 9 4 R 1 4 27 R 1 = 4 27 H 1 = 1 3 ( 2 3 ) 2 H 1 \dfrac{4H_{1}}{9} * \dfrac{9}{4R_{1}} * \dfrac{4}{27} R_{1} = \dfrac{4}{27}H_{1} = \dfrac{1}{3}(\dfrac{2}{3})^2 H_{1}

r 3 = ( 2 3 ) 3 R 1 \therefore \boxed{r_{3} = (\dfrac{2}{3})^3 R_{1}} and h 3 = 1 3 ( 2 3 ) 2 H 1 h_{3} = \boxed{\dfrac{1}{3}(\dfrac{2}{3})^2 H_{1}}

In General:

r n = ( 2 3 ) n R 1 \boxed{r_{n} = (\dfrac{2}{3})^n R_{1}} and h n = 1 3 ( 2 3 ) n 1 H 1 \boxed{h_{n} = \dfrac{1}{3}(\dfrac{2}{3})^{n - 1} H_{1}} V n = π r n 2 h n = π 3 ( 2 3 ) 3 n 1 R 1 2 H 1 = \implies V_{n} = \pi r_{n}^2h_{n} = \dfrac{\pi}{3}(\dfrac{2}{3})^{3n - 1} R_{1}^2H_{1} =

π 3 ( 2 3 ) 3 n ( 3 2 ) R 1 2 H 1 = π 2 ( 8 27 ) n R 1 2 H 1 \dfrac{\pi}{3}(\dfrac{2}{3})^{3n} (\dfrac{3}{2}) R_{1}^2H_{1} = \dfrac{\pi}{2}(\dfrac{8}{27})^n R_{1}^2H_{1}

S = n = 1 V n = π R 1 2 H 1 2 ( 8 27 ) ( 27 19 ) = \implies S = \sum_{n = 1}^{\infty} V_{n} = \dfrac{\pi R_{1}^2H_{1}}{2}(\dfrac{8}{27})(\dfrac{27}{19}) = 4 19 π R 1 2 H 1 = 4 19 ( 1 3 π R 1 2 H 1 ) 3 = \dfrac{4}{19}\pi R_{1}^2 H_{1} = \dfrac{4}{19}(\dfrac{1}{3}\pi R_{1}^2H_{1})3 =

12 19 V c o n e S V c o n e = 12 19 = a b a + b = 31 \dfrac{12}{19}V_{cone} \implies \boxed{\dfrac{S}{V_{cone}} = \dfrac{12}{19}} = \dfrac{a}{b} \implies a + b = \boxed{31} .

Note: We could have wrote: V n = 3 2 ( 2 3 ) 3 n V c o n e V_{n} = \dfrac{3}{2}(\dfrac{2}{3})^{3n} V_{cone} \implies S = V c o n e 3 2 n = 1 ( 8 27 ) n = S = V_{cone}\dfrac{3}{2}\sum_{n = 1}^{\infty} (\dfrac{8}{27})^n =

3 2 8 27 27 19 V c o n e = 12 19 V c o n e \dfrac{3}{2}\dfrac{8}{27}\dfrac{27}{19} V_{cone} = \dfrac{12}{19}V_{cone}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...